Hermeneutik Puisi “BiṭāQah Huwiyyah” dalam Antologi AurāQuz-ZaitūN Karya MahmūD DarwīSy / Hermeneutics in “BiṭāQah Huwiyyah” Poem In AurāQuz-ZaitūN Anthology by MahmūD DarwīSy - Ulfa, Hidayatun (Diwan: Jurnal Bahasa dan Sastra Arab, 2020)
هذه الرسالة بحث عن معنى الشعر "بطاقة هوية" فى ديوان أوراق الزيتون لمحمود درويش. وهدف هذه الرسالة هو تشريح معنى الموجودة في شعر "بطاقة هوية" فى ديوان أوراق الزيتون لمحمود درويش. تستخدم هذه الرسالة طريقة التخليل السميوطيقى الذي شرحه ريفاتير يعنى القراءة الرتروأكتيفة أو الهرمنيوطيقية. فنعرف من خلال قراءة رتروأكتيفة أو هرمنيوطيقية أن هذا الشعر يدل عن الإجتجاج التعنيف من رعية فلسطين لأن اسرائيل تسلط على الدولة فلسطين. وبسبب ذلك، كانت حياتهم في ويلات وأزبة. وعزموا أن يستعيدوا عنوة وطنهم لأنهم عرب، مالك الصحيح ذلك الوطن. المعنى الذي أراده الشاعر هو السلم لأنه حق أساسي للدول العالمية. أما المعنى لهذا الشعر هو لهب الهمة والنية ليقاوم ويستعد عنوة الوطن ويقوى الرجاء لوجود السلم. الكلمات الأساسية: معنى المعنى، الشعر "بطاقة هوية"، ديوان أوراق الزيتون، محمود درويش. Abstract This research discusses the meaning of the “Biṭāqah Huwiyyah” poem in the Aurāquz-Zaitūn anthology by Mahmūd Darwīsy. The aim of this study is to find out the meaning of the “Biṭāqah Huwiyyah” poem in the Aurāquz-Zaitūn anthology by Mahmūd Darwīsy. The meaning of the poem is obtained with semiotic readings raised by Riffaterre, which is hermeneutic readings. Through hermeneutic reading, this poem illustrates the demands of the Palestinian people due to the occupation of the country. This poem is a strong protest of the Palestinian people because of the occupation carried out by Israeli Zionists by forcibly seizing their homeland. The occupation resulted in them losing their homeland. Because they are in the control of other nations, suffering and misery are what they face in their daily life. However, they always hold one thing and they believe that they are the Arabs, the legal owner of the land. The message that the poet wants to convey is that peace is a basic right of every nation. The meaning of this poem is to ignite the spirit and kindle the determination to fight and reclaim the homeland that has been usurped by the usurper of the homeland and raise hopes for the realization of peace.